Context Clues Knowledge and Reading Comprehension Skills of Grade 10 Students - Jomocan, Cynthia O; Legaspi, Ma.Judy B. (Technium Education and Humanities, 2022)
This descriptive, comparative, and correlational research design aimed to determine the level of context clues knowledge and reading comprehension skills of Grade 10 students. A researcher-made validated and reliability-tested questionnaire was used to 246 randomly selected respondents composed of Grade 10 students in the three-class programs in the K-12 Curriculum. Mean and standard deviation yielded an outcome of average, which means students have acceptable knowledge in context clues and expanding results, which refers to an acceptable reading proficiency of students. Kruskal-Wallis and Post hoc Dunn’s test revealed a significant difference in the context clues knowledge and reading comprehension skills when respondents are grouped according to class programs. Spearman Rank Correlation determined that there is a significant relationship between context clues knowledge and reading comprehension skills. The findings were utilized in the preparation of enhancement/supplementary activity worksheets in strengthening the students’ ability in word meaning and reading proficiency.